Wildtype motoneurons, ALS‐Linked SOD1 mutation and glutamate profoundly modify astrocyte metabolism and lactate shuttling. Issue 4 (31st January 2017) - Madji Hounoum, Blandine; Mavel, Sylvie; Coque, Emmanuelle; Patin, Franck; Vourc'h, Patrick; Marouillat, Sylviane; Nadal‐Desbarats, Lydie; Emond, Patrick; Corcia, Philippe; Andres, Christian R; Raoul, Cédric; Blasco, Hélène
Abstract : The selective degeneration of motoneuron that typifies amyotrophic lateral sclerosis (ALS) implicates non‐cell‐autonomous effects of astrocytes. However, mechanisms underlying astrocyte‐mediated neurotoxicity remain largely unknown. According to the determinant role of astrocyte metabolism in supporting neuronal function, we propose to explore the metabolic status of astrocytes exposed to ALS‐associated conditions. We found a significant metabolic dysregulation including purine, pyrimidine, lysine, and glycerophospholipid metabolism pathways in astrocytes expressing an ALS‐causing mutated superoxide dismutase‐1 (SOD1) when co‐cultured with motoneurons. SOD1 astrocytes exposed to glutamate revealed a significant modification of the astrocyte metabolic fingerprint. More importantly, we observed that SOD1 mutation and glutamate impact the cellular shuttling of lactate between astrocytes and motoneurons with a decreased in extra‐ and intra‐cellular lactate levels in astrocytes. Based on the emergent strategy of metabolomics, this work provides novel insight for understanding metabolic dysfunction of astrocytes in ALS conditions and opens the perspective of therapeutics targets through focusing on these metabolic pathways. GLIA 2017 GLIA 2017;65:592–605 Main Points: First metabolomics study performed on primary cultures of astrocytes and motoneurons. Motoneurons induced important changes in SOD1 G93A astrocyte metabolism. Astrocytes in ALS conditions displayed a decrease of intra‐and extra‐cellular lactate.